Transcriptomic Analysis of Genes Expressed After Carotid Endarterectomy: Searching for New Pathways for Cerebral Ischemic Tolerance - Furman, Marek; Sihotsky, Vladimir; Virag, Michal; Kopolovets, Ivan; Nemethova, Miroslava; Mucha, Rastislav (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):303